2010
DOI: 10.1111/j.1365-2486.2010.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Net annual global warming potential and greenhouse gas intensity in Chinese double rice-cropping systems: a 3-year field measurement in long-term fertilizer experiments

Abstract: The impact of agricultural management on global warming potential (GWP) and greenhouse gas intensity (GHGI) is not well documented. A long-term fertilizer experiment in Chinese double rice-cropping systems initiated in 1990 was used in this study to gain an insight into a complete greenhouse gas accounting of GWP and GHGI. The six fertilizer treatments included inorganic fertilizer [nitrogen and phosphorus fertilizer (NP), nitrogen and potassium fertilizer (NK), and balanced inorganic fertilizer (NPK)], combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
263
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(331 citation statements)
references
References 73 publications
35
263
10
Order By: Relevance
“…Averaged across sampling location, aboveground dry matter was greater from XL753 (2862 g m -2 ) than from CLXL729 and Roy J, which did not differ and averaged 2488 g m -2 , while aboveground dry matter measured from CLXL745 (2649 g m -2 ) did not differ from any of the other cultivars. Although previous studies have observed a positive correlation between CH 4 emissions and aboveground dry matter [52,62,70,71], data from this study did not support that relationship, where in this case the cultivar exhibiting greater CH 4 fluxes (Roy J) was one of the lowest accumulators of aboveground dry matter. Huang et al [71] suggested that the relationship between biomass accumulation and CH 4 emissions, although correlated when examining the relationship for a single cultivar, was not strong when evaluating the relationship among different cultivars.…”
Section: Aboveground Dry Matter and Grain Yieldcontrasting
confidence: 99%
See 1 more Smart Citation
“…Averaged across sampling location, aboveground dry matter was greater from XL753 (2862 g m -2 ) than from CLXL729 and Roy J, which did not differ and averaged 2488 g m -2 , while aboveground dry matter measured from CLXL745 (2649 g m -2 ) did not differ from any of the other cultivars. Although previous studies have observed a positive correlation between CH 4 emissions and aboveground dry matter [52,62,70,71], data from this study did not support that relationship, where in this case the cultivar exhibiting greater CH 4 fluxes (Roy J) was one of the lowest accumulators of aboveground dry matter. Huang et al [71] suggested that the relationship between biomass accumulation and CH 4 emissions, although correlated when examining the relationship for a single cultivar, was not strong when evaluating the relationship among different cultivars.…”
Section: Aboveground Dry Matter and Grain Yieldcontrasting
confidence: 99%
“…Gas sampling throughout the study occurred between 0800 and 1000 hours, similar to previous studies [30,32,48,49,51,52,53], in order to prevent excessive heating within the chambers during sampling. Gas samples for flux measurements occurred on approximately weekly intervals at 7,14,21,28,35,43,49,56,63,71, and 77 days after flooding (DAF) for the flooded duration of the study.…”
Section: Gas Sampling and Analysismentioning
confidence: 99%
“…According to Ding and Cai (2003), if the soil organic carbon is less than 20 g kg , N application can stimulate soil CH4 production, the soil organic carbon were all less than 20 g kg -1 in Shenyang and Jinxian (Table 1), thus, CK treatment could enhance CH4 production and thereby CH4 emissions compared to the DR treatments. In addition, there are many early rice residues incorporated into late rice fields at Jinxian, the higher basal N application may stimulate the decomposition of rice residues that enhance CH4 production (Shang et al, 2011). At Danyang for Y Liangyou-302, DR treatments tend to reduce CH4 emissions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing nitrogen (N) fertilizer input has contributed significantly to the improvement of rice yield (Cassman et al, 2003), but simultaneously resulted in serious environmental pollution due to low N use efficiency (NUE) by improper N fertilization (Chien et al, 2009). Meanwhile, rice crop represent an important source of global methane (CH4) and nitrous oxide (N2O) emissions (Zou et al, 2009;IPCC, 2013); greenhouse gas (GHG) emissions reduction from paddy field has gained increasing concerns throughout the world Shang et al, 2011;Pittelkow et al, 2014). Thus, it is a great challenge for rice cropping to obtain high yield and NUE with low GHG emissions (Foley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, seasonal variation of methane emissions obeyed similar regularity with TASM and PMET under the influence of rice growth stage. In addition, the different patterns of methane emissions before and after mid-season drainage suggested that MSD is regarded potentially as a promising option for the mitigation of methane emissions from double-rice paddy fields as documented in the study of Shang et al (2011).…”
Section: Temporal Patterns Of Methane Emissions and Tasm And Pmetmentioning
confidence: 98%